Bounded Integration: The Regulation of Traditional and Complementary Medicine in Türkiye - Ayşe Polat (Journal of Integrative and Complementary Medicine, 2026)
Introduction: This study examines Türkiye’s recent policies on traditional and complementary medicine (T&CM), focusing on how centralized governance has expanded and regulated T&CM while maintaining it within biomedical standards. It analyzes how the state-led integration proceeds through control, standardization, and oversight, generating both formal incorporation and persistent frictions. Methods: The study is based primarily on qualitative content analysis of official Ministry of Health materials, including laws, regulations, and guidelines, which were systematically reviewed to map the regulatory architecture of T&CM; a subsequent 2026 regulatory amendment was also reviewed for continuity. In addition, 30 semi-structured interviews were conducted in 2025 with health professionals and bureaucrats involved in T&CM practice and governance. Interview data were used selectively to clarify regulatory processes and implementation dynamics. Results: Türkiye’s T&CM policy is structured around four interrelated regulatory mechanisms: (1) boundary-making by therapy and profession, (2) selective stratified expansion, (3) education and certification as gatekeeping, and (4) infrastructural and epistemic oversight. Together, these mechanisms produce “bounded integration,” in which expansion occurs through standardization and authorization while professional jurisdiction and institutional autonomy remain tightly delimited. T&CM therapies are governed through administrative, clinical, infrastructural, and scientific templates closely aligned with a physician-centered biomedical model. Discussion: Türkiye’s centralized regulatory model demonstrates how state-led integration can formalize and scale T&CM within a national health system while preserving biomedical authority. This is a bounded form of integration: Oversight remains uneven, modality-specific expertise and inspection capacity are limited, reimbursement structures are underdeveloped, and informal provision persists alongside formal authorization. Effective integration therefore requires not only standard-setting but also modality-sensitive governance capacities and greater coherence between regulatory design and clinical provision.